A completely phased diploid genome assembly for "Malbec" cultivar (Vitis vinifera L.) - Calderón, Pablo Luciano Sebastian (2021)
Most grapevine cultivars originated from the outcrossing of two genetically diverse parents, and are clonally propagated to preserve phenotypes of productive interest. Hence, cultivars are first filial generations (F1) with highly heterozygous diploid genomes, that turn challenging to assemble. "Malbec" is the main cultivar for the Argentine wine industry and it originated in France, from the outcrossing of Magdeleine Noir des Charentes and Prunelard cultivars. Based on that mother-father-offspring relationship, here we followed the algorithm implemented in the software CanuTrio to produce a phased assembly of Malbec genome. For this aim, parental cultivars? Illumina short-reads were used to sort ?Malbec? PacBio long-reads into its haploid complements, to be assembled separately. Post- assembly, bioinformatic procedures were employed to reduce the number of duplicated regions and perform sequence error corrections (using Malbec Illumina short-reads). We obtained two highly complete and contiguous haploid assemblies for Malbec, Haplotype- Prunelard (482.4 Mb size; contig N50=7.7 Mb) and Haplotype-Magdeleine (479.4 Mb size; contig N50=6.6 Mb), with 96.1 and 95.8% of BUSCO genes, respectively. We tested for the composition of both haplophases with the tool Merqury, and observed <0.13% of haplotype switches, meaning that Malbec genomic information was correctly assigned to each haploid assembly. Finally, a variant calling analysis indicated a great diversity between Malbec haplophases, with >15% of both assemblies affected by structural variations, along with 3.2 million SNPs and 0.6 million InDels. Our results indicate that this is a valid approach to assemble highly heterozygous and complex diploid genomes in a completely-phased way.